Pengaruh Lifestyle, Prestise, dan Kelompok Referensi terhadap Keputusan Pembelian pada Superindo Kota Semarang - Hera Citra Delinda; Agus Budi Santoso (Universitas Batanghari Jambi, 2023)
The development of modernization changes the behavior of purchasing power and food needs, so that purchasing decisions by consumers also change. Changes in food needs make the retail business grow rapidly. Superindo is a company in the retail sector that has been operating since 1997. The purpose of this study was to determine the influence of lifestyle, prestige, and reference groups on purchasing decisions at Superindo Semarang City. This study uses descriptive analysis and quantitative analysis. The data used is primary data with a questionnaire collection method. Data analysis using multiple linear regression analysis. The sample used is 100 respondents. The results of the study found that there was a positive and significant effect of lifestyle variables on purchasing decisions. Meanwhile, the prestige and reference group variables have no significant effect.